El hacha decimonónica: El avance silencioso de la deforestación en Costa Rica entre 1821-1900 (Revista Rupturas, 2020)
This article deals with the problem of deforestation in Costa Rica, from the early stages of independence to late 19th century. In spite of the scarce sources and statistics dealing with the issue, this work seeks to show that 19th century deforestation, though small in scale, impacted forest areas strongly, especially high-yield fine timber, and claid the foundation of the timber industry that picked up steam in the 19th century. The article also demonstrates that there was evidence on the repercussions that the exploitation pattern which was fostered by both private citizens and the State. This aspect was, however, not ignored because of the economic interests that uncultivated land and national forests represented at a time when the extraction of national resources and their subsequent sale in the market were the main objectives.
Keywords: deforestation; forests; timber; Costa Rica; conservation